PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN DONAT MADU CIHANJUANG PANDEGLANG - Damayanti, Septiana; Mulyani, Ipah (LPPM STIA Banten, 2025)
Donuts are a prevalent snack in Indonesia, with various establishments offering a range of products. Donat Madu Cihanjuang Pandeglang is a notable donut shop in Pandeglang that specializes in producing donuts with diverse variations. This study investigates the relationship between price and purchasing decisions among consumers of Donat Madu Cihanjuang Pandeglang. A quantitative survey approach was employed, utilizing both primary and secondary data. A sample of 97 respondents was selected using purposive sampling technique. Data collection was facilitated through questionnaires, and descriptive analysis was conducted to examine the data. The findings reveal a positive and significant correlation between price and purchasing decisions, suggesting that price plays a crucial role in influencing consumer behavior.